2010
DOI: 10.1007/s00234-010-0803-5
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol threshold doses for systemic complications during sclerotherapy of superficial venous malformations: a retrospective study

Abstract: Based on our findings, a maximal ethanol dose/weight ratio of 0.2 ml/kg could be considered as acceptable in VM treatment indications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…The presence of more than one needle prevents pressurising the cyst and allows free exit of the injected alcohol so that a larger amount of alcohol can be used. The recommended maximum safe amount of alcohol to use for vascular anomalies was previously 1 ml/kg [14], but recently the maximum ethanol dose/weight ratio acceptable for superficial venous malformation treatment has been lowered to 0.2 ml/kg [15]. The limit of injected alcohol in our procedures was carefully observed, and most of the alcohol was returned thanks to the multiple-needles technique.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of more than one needle prevents pressurising the cyst and allows free exit of the injected alcohol so that a larger amount of alcohol can be used. The recommended maximum safe amount of alcohol to use for vascular anomalies was previously 1 ml/kg [14], but recently the maximum ethanol dose/weight ratio acceptable for superficial venous malformation treatment has been lowered to 0.2 ml/kg [15]. The limit of injected alcohol in our procedures was carefully observed, and most of the alcohol was returned thanks to the multiple-needles technique.…”
Section: Discussionmentioning
confidence: 99%
“…Absolute alcohol (ethanol 96%) was injected in all cases. As there is a limit of alcohol to be injected [14,15], most of the alcohol used to induce sclerosis of the ABC was drained through the other needle(s), permitting larger volumes. In summary, the cysts were "washed out" with absolute alcohol.…”
Section: Methodsmentioning
confidence: 99%
“…Yakes and Baker have described desaturation, bradycardia and cardiopulmonary collapse in three adults who underwent ethanol sclerotherapy [8]. Retrospective study has suggested that the only factor significantly associated with a systemic adverse event is the ethanol dose/weight ratio per intervention [9]. Bisdorff et al [9] suggest a maximal ethanol dose/weight ratio of 0.2 ml/kg in the treatment of venous malformations with ethanol as a sclerosant.…”
Section: Discussionmentioning
confidence: 99%
“…Other complications that can arise include allergic responses, skin pigment change, cardiovascular collapse, hypotension and cardiac arrest (51,52). However, cardiovascular collapse has been obviated by limiting ethanol injected volumes to 0.15 mL/kg ideal body weight (49,53,54). Figures 2 and 3 demonstrate the effectiveness of treatment with absolute ethanol sclerotherapy.…”
Section: Ethanol Sclerotherapymentioning
confidence: 99%